Utilization of agricultural waste biomass by cellulolytic isolate Enterobacter sp. SUK-Bio - Waghmare, Pankajkumar R.; Patil, Swapnil M.; Jadhav, Sanjivani L.; Jeon, Byong-Hun; Govindwar, Sanjay P. (Agriculture and Natural Resources, 2018)
A cellulolytic bacterium was isolated from plant litter soil and identified as Enterobacter sp. SUK-Bio. This isolate was investigated for its utilization of different cellulosic materials (carboxymethyl cellulose, sugarcane trash, grass powder, sorghum husk, wheat straw and water hyacinth). Utilization of sorghum husk was comparatively more than for the other cellulosic materials used, producing higher cellulolytic and hemicellulolytic enzymes (filter paperase (0.15 U/mL), β -glucosidase (37.10 U/mL), endoglucanase (12.24 U/mL), exoglucanase (2.52 U/mL), xylanase (26.26 U/mL) and glucoamylase (33.26 U/mL)) on day 8 of incubation. Furthermore, it produced the maximum reducing sugar production (554 mg/L) at a rate of 3.84 mg/h/L. Fourier-transform infrared spectroscopy analysis of sorghum husk revealed functional groups changes and a decrease in the total crystallinity ratio after microbial degradation. The effects of supplementation of different metals additives, thermal stability and pH on cellulolytic enzymes were also studied.